2014
DOI: 10.1016/j.bone.2013.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for radiographic vertebral fractures: A potential role for the 16q24 BMD locus

Abstract: Vertebral fracture risk is a heritable complex trait. The aim of this study was to identify genetic susceptibility factors for osteoporotic vertebral fractures applying a genome-wide association study (GWAS) approach. The GWAS discovery was based on the Rotterdam Study, a population-based study of elderly Dutch individuals aged >55years; and comprising 329 cases and 2666 controls with radiographic scoring (McCloskey–Kanis) and genetic data. Replication of one top-associated SNP was pursued by de-novo genotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 84 publications
0
24
0
Order By: Relevance
“…Phenotype definition is a cornerstone of epidemiological research into vertebral fracture risk to prevent bias hampering discoveries (171)(172)(173). Moreover, merely measuring vertebral heights in clinical practice frequently leads to misdiagnosis of fracture in non-osteoporotic conditions including Scheuermann's disease (174)(175)(176).…”
Section: Vertebral Fracturesmentioning
confidence: 99%
“…Phenotype definition is a cornerstone of epidemiological research into vertebral fracture risk to prevent bias hampering discoveries (171)(172)(173). Moreover, merely measuring vertebral heights in clinical practice frequently leads to misdiagnosis of fracture in non-osteoporotic conditions including Scheuermann's disease (174)(175)(176).…”
Section: Vertebral Fracturesmentioning
confidence: 99%
“…These studies reported that VSP13B, UGT2B17 and an intergenic region within the 6p25.1 locus and 20q13.12 are associated with bone mass, osteoporosis or osteoporotic fractures (112,113,114,115,116,117).…”
Section: Other Genetic Variationmentioning
confidence: 99%
“…However, the genetic determinants of vertebral fractures are poorly understood. A previous genome-wide association study (GWAS) published by Oei and colleagues21 involving a discovery cohort of 8717 cases and 21 793 controls failed to identify any significant genetic predictors of radiographic vertebral fracture at a genome-wide significant level. However, in this study, the vertebral fractures were defined simply on the basis of morphometric analysis of spinal radiographs.…”
Section: Introductionmentioning
confidence: 98%